2018
DOI: 10.1038/s41467-017-01859-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mtDNA activates astrocytes and leads to spongiotic encephalopathy

Abstract: Mitochondrial dysfunction manifests as different neurological diseases, but the mechanisms underlying the clinical variability remain poorly understood. To clarify whether different brain cells have differential sensitivity to mitochondrial dysfunction, we induced mitochondrial DNA (mtDNA) depletion in either neurons or astrocytes of mice, by inactivating Twinkle (TwKO), the replicative mtDNA helicase. Here we show that astrocytes, the most abundant cerebral cell type, are chronically activated upon mtDNA loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 45 publications
4
57
0
Order By: Relevance
“…Both this study and the work of Ignatenko et al (2018) highlight how mitochondrial dysfunction in astrocytes can have downstream effects on neuronal function and survival. We show here that decreasing the levels of the m-AAA protease in BG is sufficient to cause noncell-autonomous morphological degeneration and to change the electrophysiological properties of PCs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Both this study and the work of Ignatenko et al (2018) highlight how mitochondrial dysfunction in astrocytes can have downstream effects on neuronal function and survival. We show here that decreasing the levels of the m-AAA protease in BG is sufficient to cause noncell-autonomous morphological degeneration and to change the electrophysiological properties of PCs.…”
Section: Discussionmentioning
confidence: 82%
“…Astrocyte‐specific deletion of Cox10 , a complex IV assembly factor, despite leading to complex IV deficiency and a respiratory deficit, caused neither cell death nor secondary neuronal degeneration, but rather increased the glycolytic metabolism of the cells (Supplie et al, ). In contrast, inactivation of the helicase Twinkle specifically in astrocytes, leading to OXPHOS deficiency and loss of mtDNA, induced a chronic activation of astrocytes, causing spongiosis, loss of neurons, and inflammation (Ignatenko et al, ). In this study, we did not find evidence of respiratory deficiency, but also observed cell‐autonomous activation of targeted astrocytes and infiltration of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor control depends on the integration of neurons in the brain. An impaired locomotor activity correlates with brain atrophy and inflammation in many mitochondrial diseases (Maltecca et al, 2009;Almajan et al, 2012;Johnson et al, 2013;Ignatenko et al, 2018). We therefore analyzed brain morphology and brain weight in NYKO mice.…”
Section: Neuroinflammation and Axonal Degeneration In Spinal Cord Of mentioning
confidence: 99%
“…This strategy was partially successful in vitro in COQ7 null yeasts, as well as in mouse and human fibroblasts with mutations in COQ7 or COQ9 (Xie et al , ; Freyer et al , ; Luna‐Sanchez et al , ). Additionally, β‐RA is a structural analogue of salicylic acid (2‐hydroxybenzoic acid), an anti‐inflammatory molecule that may be potentially valuable to reduce the neuroinflammation (Lan et al , ; Gomez‐Guzman et al , ), a factor that has been recently postulated as an essential pathomechanism and a therapeutic target in mitochondrial encephalopathies (Ignatenko et al , ), leukoencephalopathy, and neurodegenerative diseases (Eto et al , ; Liddelow & Barres, , ). Also salicylic derivate, known as salicylates, may act as mTOR inhibitors (Cameron et al , ), and this action may be therapeutic in mitochondrial diseases (Johnson et al , ).…”
Section: Introductionmentioning
confidence: 99%